Hypofractionated Radiotherapy With Volumetric Modulated Arc Therapy Decreases Postoperative Complications in Prosthetic Breast Reconstructions: A Clinicopathologic Study - Song, Seung Yong; Chang, Jee Suk; Fan, Kenneth L.; Kim, Mi Jung; Chang, Hsien Pin; Lew, Dae Hyun; Roh, Tai Suk; Roh, Hyun; Kim, Yong Bae; Lee, Dong Won (Frontiers in Oncology, 2020)
Background: Emerging radiation technologies are expected to provide a positive impact on the reduction in postoperative complications in patients receiving prosthetic breast reconstruction. This study aimed to determine whether hypofractionated radiation therapy(RT) with volumetric modulated arc therapy(VMAT) is superior to conventional RT in the setting of prosthetic reconstruction. Methods: From retrospective data collections, postoperative complications were compared for all patients with mastectomy and staged prosthetic reconstruction without RT, with hypofractionation using 40 Gy in 15 fractions with VMAT (Hypo-VMAT) or conventional RT (50 Gy over 5 weeks). After harvesting subpectoral capsules from patients with informed consents, histologic analysis including immunohistochemistry and immunofluorescence for collagen type I, α-smooth muscle actin, CD34 and CD31 expression was performed. Results: A total of 288 reconstructions without RT, 55 reconstructions with Hypo-VMAT, and 29 reconstructions with conventional RT were examined. During average follow-up period of 34.8 months, rates of overall complications were 6.3 percent in the no-radiation group, 18.2 percent in Hypo-VMAT group and 44.8 percent in conventional-RT group with significant differences (no-RT vs Hypo-VMAT: p=0.006; Hypo-VMAT vs conventional-RT: p=0.012). Levels of myofibroblasts and tissue fibrosis were lower in the Hypo-VMAT group than in conventional-RT group (p=0.016 and p=0.040, respectively), while those of progenitor cells and microvessel density were higher in the Hypo-VMAT group than in conventional-RT group (p<0.001 and p<0.001, respectively). Conclusion: We demonstrated that hypofractionated RT with VMAT served to reduce radiation-related morbidities in prosthetic reconstruction from a clinicopathologic perspective, compared to conventional RT. It may offer a practical strategy to mitigate radiation-related complications in clinical settings.